2022
DOI: 10.1038/s41416-022-02093-x
|View full text |Cite
|
Sign up to set email alerts
|

3D collagen migration patterns reveal a SMAD3-dependent and TGF-β1-independent mechanism of recruitment for tumour-associated fibroblasts in lung adenocarcinoma

Abstract: Background The TGF-β1 transcription factor SMAD3 is epigenetically repressed in tumour-associated fibroblasts (TAFs) from lung squamous cell carcinoma (SCC) but not adenocarcinoma (ADC) patients, which elicits a compensatory increase in SMAD2 that renders SCC-TAFs less fibrotic. Here we examined the effects of altered SMAD2/3 in fibroblast migration and its impact on the desmoplastic stroma formation in lung cancer. Methods We used a microfluidic device to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Likewise, our observed involvement of SMAD3 in promoting TIMP‐1 secretion more strikingly than transcription could be part of complex regulatory mechanisms affecting TIMP‐1 expression and secretion in ADC‐TAFs that remains to be fully elucidated. Interestingly, the higher levels of TIMP1 mRNA and secreted protein levels in ADC‐TAFs compared to SCC‐TAFs were attributable to the more extensive epigenetic repression of the SMAD3 promoter in SCC‐TAFs 15,40 . The heightened SMAD3 production and activation in ADC‐TAFs enhances the secretion of bioactive TGF‐β1, creating a positive feedback loop that amplifies the profibrotic activity of the TGF‐β1/SMAD3 pathway 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, our observed involvement of SMAD3 in promoting TIMP‐1 secretion more strikingly than transcription could be part of complex regulatory mechanisms affecting TIMP‐1 expression and secretion in ADC‐TAFs that remains to be fully elucidated. Interestingly, the higher levels of TIMP1 mRNA and secreted protein levels in ADC‐TAFs compared to SCC‐TAFs were attributable to the more extensive epigenetic repression of the SMAD3 promoter in SCC‐TAFs 15,40 . The heightened SMAD3 production and activation in ADC‐TAFs enhances the secretion of bioactive TGF‐β1, creating a positive feedback loop that amplifies the profibrotic activity of the TGF‐β1/SMAD3 pathway 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the higher levels of TIMP1 mRNA and secreted protein levels in ADC‐TAFs compared to SCC‐TAFs were attributable to the more extensive epigenetic repression of the SMAD3 promoter in SCC‐TAFs. 15 , 40 The heightened SMAD3 production and activation in ADC‐TAFs enhances the secretion of bioactive TGF‐β1, creating a positive feedback loop that amplifies the profibrotic activity of the TGF‐β1/SMAD3 pathway. 15 Because we showed that nintedanib attenuates the TGF‐β1/SMAD3 pathway through the partial inhibition of the TGF‐β1 type I receptor ALK5, 15 our current findings strongly support that the hyperactive TGF‐β1/SMAD3 pathway in ADC‐TAFs is responsible for their excessive production of TIMP‐1 and subsequent selective positive response to nintedanib; conversely, the low SMAD3 expression and limited TIMP‐1 production in SCC‐TAFs may confer intrinsic resistance to this drug.…”
Section: Discussionmentioning
confidence: 99%